Left atrial volume index in patients with seborrheic dermatitis - Çelik, Mehmet Semih; Arpa, Abdulkadir (The European Research Journal, 2025)
Objectives: Seborrheic dermatitis is a chronic inflammatory skin condition that primarily affects the scalp, face, and body folds. Emerging research indicates a potential link between seborrheic dermatitis and cardiac parameters. This study aims to further investigate this relationship. Methods: Fifty individuals diagnosed with seborrheic dermatitis who presented to the dermatology outpatient clinic were included, alongside a control group of healthy participants (n=30) matched by age and sex. Echocardiographic assessments were carried out for both groups, and the data were recorded using standardized forms. Results: The left atrial volume index (LAVI) was recorded as 28.3±1.24 in seborrheic dermatitis patients and 26.2±1.47 in the control group, with this difference reaching statistical significance (P